Lion Cross Point - Ono, Masatsugu, 1970-; Turvill, Angus (San Francisco, CA : Two Lines Press, 2018)
Struggling with the memory of unspeakable acts against his mother and brother, ten year-old Takeru arrives at his family's village where he befriends a caretaker and spunky neighbor and he discovers a new meaning of family and home.
Keywords: Boys -- Fiction; Families -- Fiction; Psychic trauma -- Fiction; Boys -- Fiction; Family -- Fiction; Psychological fiction